1995
DOI: 10.1177/1046496495262004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender and Communication Content on Leadership Emergence in Small Task-Oriented Groups

Abstract: This investigation examined the role played by gender and communication content in the leadership emergence process in small, task-oriented groups. Six hours of transcribed group interaction from a sample of the group deliberations of six mixed-sex groups engaged in a 4-month long decision-making project served as the database for the analysis. A simple regression analysis identified task-relevant communication as being the sole significant predictor of emerged leadership. Production of task-relevant communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
20
2
Order By: Relevance
“…Above-the-mean masculine behaviors were reported by 68 percent of the preferred leaders (those in the masculine and original androgynous categories). Hawkins (1995), reporting on a study related to this one, noted that although the notion that individuals who engaged in both task and social maintenance behaviors would emerge as leaders was "intuitively attractive," her data did not support this conclusion. She further observed that regardless of the sex of the candidate for leadership, only task-related communication was related to perceptions of emerged leadership.…”
Section: Discussion and Implications For Leadership Developmentmentioning
confidence: 90%
“…Above-the-mean masculine behaviors were reported by 68 percent of the preferred leaders (those in the masculine and original androgynous categories). Hawkins (1995), reporting on a study related to this one, noted that although the notion that individuals who engaged in both task and social maintenance behaviors would emerge as leaders was "intuitively attractive," her data did not support this conclusion. She further observed that regardless of the sex of the candidate for leadership, only task-related communication was related to perceptions of emerged leadership.…”
Section: Discussion and Implications For Leadership Developmentmentioning
confidence: 90%
“…In mixed-sex groups, sex differences in dominance behavior are less consistent. Hawkins (1995) found that men and women did not differ in verbal contributions to a group discussion. However, other researchers found that men were perceived as exhibiting greater leadership, influence, and power than women (Lord, Phillips, & Rush, 1980).…”
Section: Individual Dominancementioning
confidence: 88%
“…All three types of leader behaviors contribute to team performance because they facilitate goal accomplishment (Hawkins, 1995;Galanes, 2003;Morgeson, DeRue, & Karam, 2010;Morris & Hackman, 1969). Boundary spanning behaviors consist of coordination and consultation with outside constituents aiming to procure resources that facilitate team performance.…”
Section: Self-managing Teams As Context For Leadership Over-emergencementioning
confidence: 99%